2014
DOI: 10.24191/jeeir.v2i1.9136
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality and Its Impact on Patient Satisfaction: An Investigation in Vietnamese Public Hospitals

Abstract: This study explores the relationship between service quality and patient satisfaction in the context of the public hospitals in Vietnam, an emerging economy in Asia. Both qualitative and quantitative methods were used in this investigation. To test the hypothesized relationships, a large survey data were collected and multiple regression analyses were performed. The results provided empirical evidence for the impact of three dimensions of service quality (‘tangibles’, ‘accessibility to healthcare services’, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…The average scores on different attributes of healthcare settings varied from 3.69/5 (lowest for hospital restrooms) to 4.17/5 (highest for medical deliveries and instruction). Using a smaller sample of patients in the North of Vietnam, Nguyen and Nguyen (2014) suggested the average satisfaction score as 3.68/5 while another study reported a lower score of 3.55/5 from a Hanoi-based group of patients [6,7]. Our findings suggest that older patients, low-income patients, female patients, those with only primary level education, patients not working for private enterprises (or foreign enterprises), and rural patients reported higher levels of overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The average scores on different attributes of healthcare settings varied from 3.69/5 (lowest for hospital restrooms) to 4.17/5 (highest for medical deliveries and instruction). Using a smaller sample of patients in the North of Vietnam, Nguyen and Nguyen (2014) suggested the average satisfaction score as 3.68/5 while another study reported a lower score of 3.55/5 from a Hanoi-based group of patients [6,7]. Our findings suggest that older patients, low-income patients, female patients, those with only primary level education, patients not working for private enterprises (or foreign enterprises), and rural patients reported higher levels of overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The average scores on different attributes of healthcare settings varied from 3.69/5 (lowest for hospital restrooms) to 4.17/5 (highest for medical deliveries and instruction). Using a smaller sample of patients in the North of Vietnam, Nguyen and Nguyen (2014) suggested the average satisfaction score as 3.68/5 while another study reported a lower score of 3.55/5 from a Hanoi-based group of patients [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tangibility is the physical environment in which the provider provides service, the equipment and facilities used for delivering the service and appearance of staff (Alshatnawi and Amlus, 2016). Tangibles include medical equipment, physical care facilities and hospital physical environment and surroundings (Nguyen and Nguyen, 2014). Previously, a number of studies have found that tangibility is a significant dimension for patients to increase the level of their satisfaction (Odgerel, 2012;Alshatnawi and Amlus, 2016;Pouragha and Zarei, 2016).…”
Section: Tangibility and Outpatient Satisfactionmentioning
confidence: 99%